Evaluation of Watsons ID Application Adoption Among Generation Z Users: Applying the UTAUT2 - Byanca Rebecca Yocelyn Sitompul; Anita Wulansari; Eristya Maya Safitri (Komunitas Dosen Indonesia, 2025)
The rapid advancement of digital technology has significantly transformed the retail landscape, particularly within the beauty and health e-commerce sector. In response to this shift, the Watsons ID application was developed to provide a fast, convenient, and feature-rich platform for online shopping. This study examines how Generation Z consumers in Indonesia adopt and use the Watsons ID application by applying the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework. A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM), with data collected from 410 respondents through purposive sampling. The research specifically targeted Indonesian Generation Z users who have experience with the Watsons ID application. The findings indicate that Performance Expectancy, Social Influence, Price Value, and Habit have a significant positive impact on users' intention to use the application. Furthermore, Habit and Behavioral Intention positively influence actual usage behavior. Conversely, Effort Expectancy and Facilitating Conditions do not show a significant effect on Behavioral Intention, and Facilitating Conditions also do not affect Use Behavior. These insights provide valuable guidance for e-commerce developers and beauty retailers seeking to optimize digital strategies, enhance user experience, and strengthen customer engagement specifically targeted toward Generation Z consumers in the Indonesian market.